KEDUDUKAN HAK ATAS AHLI WARIS ANAK KANDUNG NON MUSLIM DI INDONESIA DALAM PERSPEKTIF HUKUM ISLAM - Agus Purnomo (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTOne of the issues of inheritance which is still being debated is, heirs of different religions, both between Muslims (as heirs) and non-Muslims (as heirs) or vice versa. This is considering life in the present, especially as Indonesia as a heterogeneous nation (diverse) has increasingly developed and complex, where marriages of different religions or "phenomena" of converting to a family are increasingly widespread, so this will have very real implications. and serious when faced with inheritance issues.In examining the problem of inheritance distribution in this study specifically for non-Muslim biological children who will be studied comprehensively through normative juridical research that is Library Research is research with data sources derived from literature literature.The result of this study is the position of heirs of non-Muslim biological children in Islamic Law and Islamic Law Compilation, which is not yet explicitly regulating the division of inheritance of different religions, but the hadith and majority of scholars agree that there is no inheritance part for heirs of different religions. Then what about the obligatory testament itself in Islamic law, evidently in the law Islamic law does not know about the testamentary obligatory but only knows about the will or grant, about the obligatory testament governed in the Compilation of Islamic Law but only limited to adopted children and adoptive parents for it as a way out of this problem the Supreme Court through its ruling gave a mandatory will for non-Muslim heirs as a solution to this problem. Keywords: Natural Child Heirs, Religious Differences, Mandatory Wills